Culturally Relevant Practice Frameworks and Application in Adult Education - Patrice B. French (Adult Education Research Conference, 2019)
This literature review examines the use of three frameworks on culturally relevant practices influence on adult education, by comparing framework components to andragogical principles and process elements.
Keywords: culturally relevant practices; andragogy